(untitled) (Élisée - Revista de Geografia da UEG, 2020)
Paleochannels as evidence of historic channel changes, can be formed by intrinsic and extrinsic factors of its basin, occurring over varied temporal scales. Its mapping by remote sensing is important to understand these features meaning, increasing informations for environmental management, because this tools allows separate targets based on its spectral response upon multispectral indices application. Some multispectral indices as Tasseled Cap and its product Wetness, NDMI and MNDWI might highlight soil/vegetation moisture and water features respectively. Based on that, this paper aims to utilize assess these three indices aplicability over Landsat 8 images to identify paleochannels over a floodplain stretch of the low Rio Claro - GO, Araguaia river affluent, which holds paleochannels of different environmental characteristics. As a result, the indices were satisfactory, showing resemblance and potentialities according with environmental characteristics of the features. Based on that, it’s been verified that rio Claro main channel have experienced differents process of channel abandonment. Furthermore, its application allowed interpretations about fluvial migration processes over the studied area, considering that the area has moist environments diversity that enable its mutual application.